Droplet digital polymerase chain reaction for rapid broad-spectrum detection of bloodstream infections - Wouters, Y; Dalloyaux, D; Christenhusz, A; Roelofs, HMJ; Wertheim, HF; Bleeker-Rovers, CP; Te Morsche, RH; Wanten, GJA (Wiley, 2019)
The droplet digital polymerase chain reaction (ddPCR) is a novel molecular technique that allows rapid quantification of rare target DNA sequences. Aim of this study was to explore the feasibility of the ddPCR technique to detect pathogen DNA in whole blood and to assess the diagnostic accuracy of ddPCR to detect bloodstream infections (BSIs), benchmarked against blood cultures. Broad-range primers and probes were designed to detect bacterial 16S rRNA (and Gram stain for differentiation) and fungal 28S rRNA. To determine the detection limit of ddPCR, 10-fold serial dilutions of E. coli and C. albicans were spiked in both PBS and whole blood. The diagnostic accuracy of ddPCR was tested in historically collected frozen blood samples from adult patients suspected of a BSI and compared with blood cultures. Analyses were independently performed by two research analysts. Outcomes included sensitivity and specificity of ddPCR. Within 4 h, blood samples were drawn, and DNA was isolated and analysed. The ddPCR detection limit was approximately 1–2 bacteria or fungi per ddPCR reaction. In total, 45 blood samples were collected from patients, of which 15 (33%) presented with positive blood cultures. The overall sensitivity of ddPCR was 80% (95% CI 52–96) and specificity 87% (95% CI 69–96). In conclusion, the ddPCR technique has considerable potential and is able to detect very low amounts of pathogen DNA in whole blood within 4 h. Currently, ddPCR has a reasonable sensitivity and specificity, but requires further optimization to make it more useful for clinical practice.